Metaestudo sobre lideranças escolares no Brasil na perspectiva da gestão democrática de 2018 a 2022 - Esposito, Ícaro Rodrigo (Universidade Federal de São Carlos, 2023)
This dissertation reports on an investigation carried out within the Group of Studies and Research on School Organization: Democracy, Human Rights and Principals’ Training – DEFORGES, having as its theme school leaderships in a public-school democratic administration perspective. The general objective was to map out scientific productions on school leadership in Brazilian basic education to identify possibilities for strengthening schools’ democratic administration. The specific objective was to analyze and systematize its theoretical references, methodologies, and results. The guiding question was: how are school leaderships configured in Brazil, based on the scientific production found in Brazilian digital databases, regarding strengthening the public schools’ democratic administration? From a methodological point of view, this was a qualitative, descriptive, and analytical meta-study. The databases consulted were the CAPES Journals, Theses and Dissertations Portal, the Brazilian Digital Library of Theses and Dissertations – BDTD and the Google Scholar search engine, in the time frame from 2018 to 2022. The corpus of analysis comprised 18 works – 10 articles, six dissertations and two theses, which were selected through bibliographical research procedures, with analytical syntheses being elaborated for each one of them. Then, the sections dedicated to the metamethod, meta-analysis and metatheory were developed, the latter using the technique of content analysis of the data, for which the MAXQDA 22 software was used. The analysis of the corpus enabled an advance in the theme of school leaderships, present in some works, with democratic assumptions, that is, of collective participation, decision distribution of and awareness of those involved. In this democratic context, school leaders can emerge in all school segments – in addition to the administrative one, as it was evidenced in this dissertation, including teaching leadership.
Meta-study on school leadership in Brazil from the perspective of democratic management from 2018 to 2022
Keywords: Lideranças escolares; Gestão democrática da escola pública; Produções acadêmicas; School leadership; Democratic management of the public school; Academic productions; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL